Impact of gastro-oesophageal reflux disease symptoms on COPD exacerbation. Issue 11 (5th June 2008) - Terada, K; Muro, S; Sato, S; Ohara, T; Haruna, A; Marumo, S; Kinose, D; Ogawa, E; Hoshino, Y; Niimi, A; Terada, T; Mishima, M
Abstract : Background: The association between gastro-oesophageal reflux disease (GORD) and chronic obstructive pulmonary disease (COPD) exacerbation has so far remained unclear. Objective: To prospectively establish the clinical significance of GORD symptoms on exacerbation. Methods: 82 patients with COPD and 40 age matched controls were enrolled in this study. Symptoms were evaluated by a questionnaire using the Frequency Scale for the Symptoms of GORD (FSSG). Patients with COPD were prospectively surveyed for 6 months, and episodes of exacerbation were identified using a diary based on modified Anthonisen's criteria. Exhaled breath condensate (EBC) pH was measured in both groups, and induced sputum was evaluated in patients with COPD. Results: Positive GORD symptoms were reported in 22 (26.8%) patients with COPD and in five (12.5%) controls (p = 0.10). The frequency of exacerbations was significantly associated with the FSSG score (p = 0.03, r = 0.24, 95% CI 0.02 to 0.43). Multiple regression analysis revealed that GORD symptoms were significantly associated with the occurrence of exacerbations (p<0.01; relative risk 6.55, 95% CI 1.86 to 23.11). EBC pH was inversely correlated with FSSG score in both groups (p = 0.01, r = –0.37, 95% CI –0.55 to −0.14 in patients with COPD, and p<0.01, r = –0.45, 95% CI –0.67 to −0.16 in control subjects). Conclusions: GORD symptoms were identified as an important factor associated with COPD exacerbation.